Finite element analysis of circular arch bridges with variable cross sections - Amnart Ngarmpaibulsombat; Worsak Kanok-Nukulchai; Gupta, Satyendra P.; Pichai Nimityongskul; Government of Austria (Bangkok : Asian Institute of Technology, 1998)
In this study, a parametric study of a thin-walled box section arch is conducted using finite element model. Bilinear degenerated shell element is employed for the analysis of the circular arch, prismatic as well as non-prismatic, with and without diaphragms. Due to the relative weakness in the transverse direction of the arch, special attention is given to the role of the arch parameters in providing lateral stiffness. These parameters are the horizontal component of the doubly curved arch, and the thickness ratio of the top and bottom plates over the side plates. From the study, it was found that diaphragms are very important to provide cross-sectional rigidity and lateral stiffness. With diaphragms, the thin-walled arch can be treated like a curved beam. It was also concluded that given that the top and bottom plates are relatively thin compared to the side plates, it will be more effective and economic to use a doubly curved arch with concave section than prismatic cross-section that consume more material without significant contribution to lateral stiffness.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1998
Keywords: Bridges, Arched; Finite element method